That thing you do! [videorecording (DVD)] - Hanks, Tom; Scott, Tom Everett, 1970-; Tyler, Liv (20th Century Fox Home Entertainment, 2007)
Appliance salesman Guy Patterson fills in for an injured dummer when the band The Wonders completes in a talent show. After Guy injects a Merseybeat rhythm into lead singer Jimmy's ballad, the song's undeniable pop power flings the group into a brief whirlwind of success.